(untitled) (Research, Society and Development, 2021)
The search for a pleasant and harmonious dental aesthetic has led to a significant increase in research on new materials and techniques for direct restorations that optimize the quality, achieving almost imperceptible patterns of the tooth-restoration interface, as well as restoring the shape and function of the tooth with less wear of the dental structure when compared to indirect means. In this sense, the aim of this study was to perform a literature review on anterior direct veneers exposing their advantages and limitations compared to indirect veneers. Articles published in LILLACS (Latin American and Caribbean Literature on Health Sciences), BBO-ODONTOLOGIA (Brazilian Bibliography of Dentistry), MEDLINE (Medical Literature Analysis and Retrieval System Online) and PUBMED (National Library of Medicine) were analyzed. Through the results obtained in this literature review, where 14 (fourteen) articles were selected for the study, it was possible to verify that through the improvement of adhesive systems and composite resins, direct veneers can restore tooth color, shape and functionality, allowing aesthetic and functional rehabilitation of the dental elements, harmonizing them with the other orofacial components of the patient, but it is essential to make a correct diagnosis and apply a good technique to achieve a satisfactory result. We conclude that direct composite resin veneers are efficient for rehabilitating dental elements, allowing a pleasant esthetic, as well as adequate function. They are considered a conservative procedure, lower cost and faster when compared to indirect ceramic veneers.